Aspek Pidana Cyberstalking Sebagai Salah Satu Bentuk Cybercrime - Muhammad Maulana Zaki (Faculty of Law, Universitas Airlangga, 2022)
Abstract Technology is developing, the pattern of interaction between humans is also changing. Internet is a new world where humans interact, without the limitations of distance and time. but the internet cannot be separated from dangerous actions, one of which is Cyberstalking. An act of cybercrime that is usually not considered dangerous but if it harms the victim it can potentially become a criminal act and the absence of rule causing the legality problem Based on this background, the purpose of this study is emphasizing criminal aspect by qualifying cyberstalking as maliciuos act. Continued by analyzing the criminal responsibilty of the perpetrators and the legal evidence of Cyberstalking. The research method used is a legal doctrinal method with a statutory approach, conceptual approach and comparative approach. Keywords: Cyberstalking; Criminal aspect; Cybercrime. Abstrak Teknologi berkembang, pola interaksi antar manusia juga berubah. Internet adalah hal baru dunia tempat manusia berinteraksi, tanpa batasan jarak dan waktu. namun internet tidak lepas dari tindakan-tindakan yang berbahaya, salah satunya adalah Cyberstalking yangsebuah tindakancybercrime yang biasanya tidak dianggap berbahaya namun jika merugikan korban maka dapat berpotensi menjadi tindakan kriminal dan kekosongan aturannya menimbulkan problematika dalam legalitasnyaBerdasarkan dari latar belakang tersebut tujuan penelitian ini adalah menitikberatkanaspek pidana nya yakni dengan menganalisis kualifikasi cyberstalking sebagai tindakan yang dicela. Dilanjutkan pertanggungjawaban dan pembuktian dari pelaku kejahatan Cyberstalking. Metode penilitian yang digunakan adalah hukum normatif dengan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan perbandingan Kata Kunci: Cyberstalking; Aspek Pidana; Cybercrime.